Enhancing the Students’ Grammar Achievements of Conditional Sentences by Using Quizizz Platform in Senior High School - Moh. Mansur; Dian Fadhilawati (JARES (Journal of Academic Research and Sciences), 2021)
Grammar Instruction in MAN Kota Blitar especially in class XI IPS 2 is not satisfactory. Because of that reason, the reserchers conducted a classroom action research to investigate 35 learners’ Grammar improvement of conditional sentence by using quizizz platform. The procedures of this research included: Planning, Acting, Observing, and Evaluating. For gaining the data, the researchers used Test and Questionnaire.The finding revealed that the Quizizz platform could enhance the stuudents’ achievement as well as gained positive views from students. Therefore, the researchers suggest the English teachers to use Quizizz Platform for creating joyful learning in or outside of the classroom.